Peningkatan Hasil Belajar Siswa dalam Pembelajaran Pkn dengan Menggunakan Model Koperatif Tipe STAD di MIN - Afriani, Evi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The purpose of this research is to describe the increasing of learning result in PKN subject using STAD type model in IV class Pasar Baru Bayang, with subject of research is students of IV class that amounted to 20 students. The result of this research show that average I cycle RPP acquisition is 80.35% which is in good category, II cycle is 85.71% which also in good category. Assessment of teacher aspect I cycle acquisition is 79.16% in average which is in fair category and II cycle acquired 83.33% in average which is in good category. Student’s learning result in I cycle is 69.45% in average and II cycle is 76.3% in average.     Kata Kunci: hasil belajar PKn; model STAD